(untitled) (Journal of Engineering, 2025)
A road network uses rigid pavement for various purposes, still, it can face several challenges, including cracking from temperature changes, shrinkage, load stress application, brittleness, and flexural and tensile weakness. The thickness of rigid pavement significantly influences its performance and durability. A thicker slab distributes weight more effectively on the subgrade; however, greater thickness significantly raises construction costs, requires more resources, and negatively impacts the natural environment. The purpose of this study is to find out how adding a 1% volume fraction of steel and glass fiber in single and hybrid shapes changes the mechanical properties of concrete and pavement thickness. The compressive strength test, the flexural strength test, and the splitting tensile test were used to investigate the change in mechanical properties and The software (EMS) was selected to compute the thickness of the concrete pavement. The findings indicated a significant improvement in the mechanical characteristics resulting from the reinforcement of concrete with fibers. This was shown by a modest increase in compressive strength, reaching 9.1% after 90 days, along with significant enhancements in tensile and flexural strength, achieving 72.5% and 70% after 90 days, respectively. These adjustments, along with the use of PCASE EMS, resulted in a 30% decrease in thickness relative to the reference mixture.